Use of negative pressure therapy in closed surgical incisions of post-bariatric dermolipectomy - Lara Gomes Faistel; Dilmar Francisco Leonardi (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Negative pressure therapy gains ground in surgical practice as an intervention to improve healing. Post-bariatric patients undergoing abdominal dermolipectomy are at increased risk of local complications. There is a notable dearth of current Brazilian studies on this. This study aims to analyze the presence of complications in patients undergoing post-bariatric dermolipectomy surgery with negative pressure dressing in closed surgical incisions. Method: Descriptive study that evaluated complications of surgical incisions in 20 patients undergoing post-bariatric dermolipectomy surgery with negative pressure therapy. Data tabulated in Windows Excel software and analyzed in the Statistical Package for the Social Sciences 18.0 program. Qualitative variables were presented in simple frequency and quantitative as mean, standard deviation, and amplitude. CEP-UNISUL approved the study. Results: 20 patients undergoing negative pressure therapy, 80% (n=16) female, mean age 39.55 years (±9.08). Anchor incision was chosen in 70% (n=14) of the surgeries, with an average tissue removal of 1940 grams (±710.37) and hospitalization time of 40.20 hours (±19.18), corresponding to 1,66 daily. Only 15% (n=3) of patients had complications (dehiscence, seroma, and hematoma, which occurred in the same proportion). There was no case of necrosis. Conclusion: The use of negative pressure therapy in closed surgical incisions of post-bariatric dermolipectomy seems to contribute to reducing postoperative complications.